Palestinian Public Opinion Polls No. 15 - (:unkn) unknown (An-Najah National University/ Opinion Polls and Survey Studies Unit, 2005)
The explosion that took place in Jabalia refugee camp on Sep. 23 ‎during a military parade organized ‎by Hamas celebrating the Israeli ‎withdrawal from the Gaza Strip. The explosion took the lives of 20 ‎‎citizens.‎ The tense relationship between the Palestinian Authority and Hamas ‎on the background of the ‎explosion and the armed confrontations ‎between the two sides which were reconciled later on.‎ The launching of rockets from the Gaza Strip on Israel following the ‎explosion and the Israeli threat ‎to retaliate with an unprecedented ‎harmful response if these rockets do not stop.‎ A covenant of honor is signed on oct. 17 by 12 Palestinian factions ‎excluding Hamas regarding ‎commitment to well-defined principles ‎before and after the second legislative elections.‎ An Israeli rejection, backed by the Americans, to the participation of ‎Hamas in the coming ‎legislative elections. The Palestinian Authority ‎and the Palestinian factions consider the Israeli ‎rejection an ‎interference in Palestinian internal affairs. They emphasize the ‎importance of the ‎participation of all Palestinians in the elections ‎which will be held on January 25, 2005.‎ The continuous Israeli incursions and assassinations; several leaders ‎and subjects of the Palestinian ‎factions in the West Bank and the ‎Gaza Strip were assassinated.‎ Reaching an agreement between Israelis and Palestinians with ‎American mediation to reoperate ‎the border crossing of the Gaza ‎Strip especially Rafah crossing with Palestinian suspensions that ‎the ‎agreement may not be honored by the Israelis. Hamas considered the ‎agreement a weak one ‎which reduces the Palestinian sovereignty and ‎hurts the dignity of Palestinians.‎